Updated ILAE evidence review of antiepileptic drug efficacy and effectiveness as initial monotherapy for epileptic seizures and syndromes - Glauser, Tracy; Ben‐Menachem, Elinor; Bourgeois, Blaise; Cnaan, Avital; Guerreiro, Carlos; Kälviäinen, Reetta; Mattson, Richard; French, Jacqueline A.; Perucca, Emilio; Tomson, Torbjorn (Epilepsia (Copenhagen), 2013)
Summary The purpose of this report was to update the 2006 International League Against Epilepsy (ILAE) report and identify the level of evidence for long‐term efficacy or effectiveness for antiepileptic drugs (AEDs) as initial monotherapy for patients with newly diagnosed or untreated epilepsy. All applicable articles from July 2005 until March 2012 were identified, evaluated, and combined with the previous analysis (Glauser et al., 2006) to provide a comprehensive update. The prior analysis methodology was utilized with three modifications: (1) the detectable noninferiority boundary approach was dropped and both failed superiority studies and prespecified noninferiority studies were analyzed using a noninferiority approach, (2) the definition of an adequate comparator was clarified and now includes an absolute minimum point estimate for efficacy/effectiveness, and (3) the relationship table between clinical trial ratings, level of evidence, and conclusions no longer includes a recommendation column to reinforce that this review of efficacy/evidence for specific seizure types does not imply treatment recommendations. This evidence review contains one clarification: The commission has determined that class I superiority studies can be designed to detect up to a 20% absolute (rather than relative) difference in the point estimate of efficacy/effectiveness between study treatment and comparator using an intent‐to‐treat analysis. Since July, 2005, three class I randomized controlled trials (RCT) and 11 class III RCTs have been published. The combined analysis (1940–2012) now includes a total of 64 RCTs (7 with class I evidence, 2 with class II evidence) and 11 meta‐analyses. New efficacy/effectiveness findings include the following: levetiracetam and zonisamide have level A evidence in adults with partial onset seizures and both ethosuximide and valproic acid have level A evidence in children with childhood absence epilepsy. There are no major changes in the level of evidence for any other subgroup. Levetiracetam and zonisamide join carbamazepine and phenytoin with level A efficacy/effectiveness evidence as initial monotherapy for adults with partial onset seizures. Although ethosuximide and valproic acid now have level A efficacy/effectiveness evidence as initial monotherapy for children with absence seizures, there continues to be an alarming lack of well designed, properly conducted epilepsy RCTs for patients with generalized seizures/epilepsies and in children in general. These findings reinforce the need for multicenter, multinational efforts to design, conduct, and analyze future clinically relevant adequately designed RCTs. When selecting a patient's AED, all relevant variables and not just efficacy and effectiveness should be considered.